Clinical Comparison of the Subepithelial Connective Tissue versus Platelet-Rich Fibrin for the Multiple Gingival Recession Coverage on Anterior Teeth Using the Tunneling Technique. (13th June 2017) - Pazmiño, Victor Fabrizio Cabrera; Rodas, Miguel Agusto Riquelme; Cáceres, Carlos David Barrios; Duarte, Guillermo Gustavo Renault; Azuaga, Melanie Vanesa Cano; de Paula, Bruna Luísa; Caliente, Eliana Aparecida; Soares, Simone; Silveira, Elcia Maria Varize
Abstract : The aim of this study was to evaluate and compare, clinically, the efficiency of the subepithelial connective tissue graft (SCTG) and platelet-rich fibrin (L-PRF) using the tunnel technique to cover the multiple gingival recessions on anterior teeth, in the same patient. Within the limits of this study, we conclude that both SCTG and L-PRF proved to be reliable options for the treatment of gingival recessions, efficiently supporting the biological and aesthetic demand, stimulating the periodontal tissues' health, and bringing reliable and highly predictable results.